Apprenticeship Culture among Traditional Tailors in Atiba Local Government Area in Oyo State, South-Western, Nigeria - Jawando, Jubril Olayiwola; Oluranti , Samuel; Odunaike, Bolawale (Richtmann Publishing, 2012)
This paper assessed the apprenticeship culture among the traditional tailors in Atiba Local Government Area of Oyo State.Adopting qualitative methods, specifically the Focus Group Discussion and In-depth Interview, the study found that apprenticeshipamong the traditional tailors is shaped by common framework of guiding principles. The nature of traditional apprenticeship culture alsovaries among the tailors. In addition the traditional apprentice also possesses some unique characteristics that distinguished them fromthe Ibo apprentice. Furthermore, they have unbreakable relationships that make for their unity against masters. The paper suggestsgovernment involvement through adequate supply of electricity, soft loan, training and retraining for masters as well as the organizationof extra mural centres for them. The tailors and their apprentices should be alive to new ways of doing their trade so as to be much moremarketable.